Growth potential for CO2 emissions transfer by tariff reduction. (7th February 2019) - Islam, Moinul; Kanemoto, Keiichiro; Managi, Shunsuke
Abstract: A reduction in tariff barriers facilitates the relocation of factories to countries with less stringent environmental regulations. There has been rapid growth in the transfer of emissions from developing to developed countries through international trade over the last 30 years. However, almost all countries still maintain their tariff barriers, and these tariffs limit the potential to increase carbon dioxide (CO2 ) emissions transfers. This paper aims to examine the impact of tariff reduction on the CO2 embodiment associated with the imports of the group of twenty (G20) countries. The econometric analysis uses disaggregated tariff data and CO2 embodied emissions data from 1990 to 2013. The findings reveal that a 1% tariff cut by G20 countries for mining gas, manufactured machinery, metal, and other mining imports would result in 2779, 1747, 1453, and 1018 tons of CO2 emissions, respectively. We show that a tariff cut would increase the embodied CO2 emissions significantly for most of the manufacturing and mining sectors. Here, we find there is a 3.5%–232.2% growth potential of CO2 emissions embodied in imports, depending on whether G20 countries abolish tariff barriers. This scenario makes it difficult to achieve national emissions reduction targets and to implement national environmental policy.